Are Aortic Root and Ascending Aorta Diameters Measured by the Pediatric versus the Adult American Society of Echocardiography Guidelines Interchangeable? - Maria Luz Servato (MDPI AG, 2021)
Ascending aorta diameters have important clinical value in the diagnosis, follow-up, and surgical indication of many aortic diseases. However, there is no uniformity among experts regarding ascending aorta diameter quantification by echocardiography. The aim of this study was to compare maximum aortic root and ascending aorta diameters determined by the diastolic leading edge (DLE) and the systolic inner edge (SIE) conventions in adult and pediatric patients with inherited cardiovascular diseases. Transthoracic echocardiograms were performed in 328 consecutive patients (260 adults and 68 children). Aorta diameters were measured twice at the root and ascending aorta by the DLE convention following the 2015 American Society of Echocardiography (ASE) adult guidelines and the SIE convention following the 2010 ASE pediatric guidelines. Comparison of the diameters measured by the two conventions in the overall population showed a non-significant underestimation of the diameter measured by the SIE convention at root level of 0.28 mm (CI −1.36; 1.93) and at tubular ascending aorta level of 0.17 mm (CI −1.69; 2.03). Intraobserver and interobserver variability were excellent. Maximum aorta diameter measured by the leading edge convention in end-diastole and the inner edge convention in mid-systole had similar values to a mild non-significant underestimation of the inner-to-inner method that permits them to be interchangeable when used in clinical practice.